Quasi-greedy bases for sequences with gaps. (July 2021) - Berasategui, M.; Berná, P.M.
Abstract: In this paper, we establish new results in the theory started by T. Oikhberg in Oikhberg (2018) where the author joins greedy approximation theory with the use of sequences with gaps. Concretely, we study and provide some answers to three open questions related to quasi-greedy bases for sequences with gaps posed in Oikhberg (2018)[Section 6].